Inheritance of Fruit Detachment Force and Its Association with Pedicel Characters in Capsicum annuum L. - Ridwan Setiamihardja (Zuriat, 1991)
Low Fruit Detachment Force (FDF) is necessary to harvest fruit-producing crops to allow low fruit damage during harvest. FDF was evaluated in the Serrano x KRG family; it appeared that FDF inherited quantitatively with dominant gens action but mainly additive. Correlation coefficient between FDF with pedicel diameter was positive, and negative with pedicel index, and both significant at the 1 percent level.